The Relationship Between Parenting Patterns and Moral Development of Preschool-Aged Children - Zatihulwani, Eliza Zihni (Universitas Airlangga, 2025)
Introduction: Parents have their own parenting style in educating, guiding and disciplining children which is relatively consistent from time to time, and this can affect the moral development of children. There are three types of parenting styles used, namely democratic, authoritarian, and permissive. The purpose of this study is to analyze the relationship between parenting style and the moral development of preschool-age children. Method: The method of this study is correlation analysis with a cross-sectional approach with a population of 35 respondents. The research sample was 32 respondents from parents of preschool children aged 4-6 years with purposive sampling. The research instrument for parental parenting and children's moral development uses a questionnaire. Data analysis using the Chi-Square test. Results: The results showed that most parents had a democratic parenting style in 19 respondents (59.4%), and the moral development of children mostly showed good moral development in as many as 17 respondents (53.2%). The results of the Chi-Square analysis of parental parenting with children's moral development showed that the p-value of < α was 0.011<0.05 which means that there is a relationship between parental parenting and the moral development of preschool-aged children. Conclusion: Parenting plays a pivotal role in shaping the moral development of preschool-aged children. The application of an appropriate parenting style is essential for effectively guiding and educating children during this critical stage of development. Given the unique characteristics and needs of early childhood, this study highlights the importance of adopting a democratic parenting style—characterized by warmth, responsiveness, and appropriate boundaries—as a means of fostering positive moral growth. This study underscores the urgency of promoting parenting approaches that support moral understanding, empathy, and pro-social behavior. Future research is encouraged to further explore and develop intervention strategies and educational programs aimed at enhancing children’s moral development through supportive parenting practices.